The Science of jurisprudence in the Islamic East (132-656 A.H/ 749-1288) - AbdulAmeer, Maha Waddah (Al-Adab Journal, 2022)
The title of the research is the Science of jurisprudence in the Islamic East (132-656 A.H/ 749-1288). Study Contents: The First topic the science of jurisprudence and jurists in the Islamic East. The Second topic: The Science of jurisprudence and jurisprudence Schools in the Islamic East. The third study: Figh flags in the Islamic East. The Science of jurisprudence is one of the most important human Sciences that Arab Muslims Knew because of its Connection with Islamic law and Consequently its Conuection to People’s daily lives. Several Secs appeared in the Islamic East that were associated with the Science of jurisprudence, Suchas the Shiite, Hanafi and shafi’I Sects, and the shafi’I Sect was the most prevalent of these Sects in the Islamic East. The Science of jurisprudence was in fluenced by these schools of thought, as it ranged between the caliphs and the Abbasid leaders between ebb and flow. It is worth noting the emergence of agroup of the most Famous Scholarls in the fild of jurisprudence in the Islamic East at that time, Such as Al-Matridi, al- Ghazali, Al- Shashi and others. The Studied and thaught in major Schools, as well as Compiled major works that coutituted an important resource of human. Heritage.